IMPACT OF MATERIAL PLANNING ON THE REDUCTION OF LOGISTICS COSTS IN THE MANUFACTURING INDUSTRY - Contreras, Porfirio Tamayo; Hernández, Jessica Yadira Fuerte (Seven Editora, 2026)
The study analyzes the impact of material planning on the reduction of logistics costs within the manufacturing industry, highlighting the strategic role of tools such as Material Requirements Planning (MRP). Using a quantitative, correlational, and cross-sectional approach applied to 32 manufacturing companies in Guanajuato, the relationship between material management, inventories, transportation, and storage was evaluated. The results showed that adequate material planning significantly contributes to reducing logistics costs, optimizing inventories, decreasing obsolescence, and improving operational coordination. Likewise, it was identified that synchronization between supply, production, and distribution promotes organizational efficiency. However, limitations still persist regarding the reduction of urgent transportation and the achievement of full logistics integration. It is concluded that material planning constitutes a strategic element for strengthening the competitiveness and resilience of manufacturing organizations.